2019
DOI: 10.1002/jmd2.12043
|View full text |Cite
|
Sign up to set email alerts
|

Individual heat map assessments demonstrate vestronidase alfa treatment response in a highly heterogeneous mucopolysaccharidosis VII study population

Abstract: Mucopolysaccharidosis (MPS) VII is an ultra‐rare, progressively debilitating, life‐threatening lysosomal disease caused by deficiency of the enzyme, β‐glucuronidase. Vestronidase alfa is an approved enzyme replacement therapy for MPS VII. UX003‐CL301 was a phase 3, randomized, placebo‐controlled, blind‐start study examining the efficacy and safety of vestronidase alfa 4 mg/kg intravenously administered every 2 weeks to 12 patients with MPS VII. Due to the rarity of disease, broad eligibility criteria resulted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…Baseline abnormalities and key mobility assessments were displayed using a heat map‐like display. 14 Given the absence of any previous reports of clinical outcome assessment use in ARG1‐D, baseline deficits and clinical response definitions were based on literature insights from other relevant mobility impacting conditions and expert opinions. Baseline deficits were defined as: 6MWT: below the lower fifth percentile; GMFM‐D: <35 of 39; GMFM‐E: <68 of 72; ABAS‐3: ≤85.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Baseline abnormalities and key mobility assessments were displayed using a heat map‐like display. 14 Given the absence of any previous reports of clinical outcome assessment use in ARG1‐D, baseline deficits and clinical response definitions were based on literature insights from other relevant mobility impacting conditions and expert opinions. Baseline deficits were defined as: 6MWT: below the lower fifth percentile; GMFM‐D: <35 of 39; GMFM‐E: <68 of 72; ABAS‐3: ≤85.…”
Section: Methodsmentioning
confidence: 99%
“…AEs, vital signs, and laboratory tests including PD assessments were summarized. Baseline abnormalities and key mobility assessments were displayed using a heat map‐like display 14 . Given the absence of any previous reports of clinical outcome assessment use in ARG1‐D, baseline deficits and clinical response definitions were based on literature insights from other relevant mobility impacting conditions and expert opinions.…”
Section: Methodsmentioning
confidence: 99%
“…Two studies on MPS I and MPS II identified the amelioration of ROM as the main cause of improvements in ADL and consequently in QoL [34,45]. Improvement in mobility was seen in 6 of 12 MPS VII patients treated with vestronidase alfa and 6 out of 12 patients showed fine motor issues and self-care improvement [21,157]. Conversely, Cox-Brinkman et al did not find any ROM improvement in MPS I after one year of treatment with laronidase [94] and Guarany et al did not see any difference between treated and not-treated patients with different MPSs [95].…”
Section: Jointsmentioning
confidence: 99%
“…Vestronidase alfa concentrations declined multi-exponentially following infusion, and there was no evidence of accumulation with QOW dosing. A pharmacokinetic-pharmacodynamic modelling study that included subjects in this study supported the vestronidase alfa dosing regimen of 4 mg/kg QOW [ 5 , 6 , 8 , 9 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Vestronidase alfa (recombinant human β-glucuronidase) is an enzyme replacement therapy approved in the United States for the treatment of MPS VII in children and adults, in Europe for non-neurological manifestations of MPS VII, and in Brazil [ [5] , [6] , [7] ]. In a randomized, placebo-controlled, phase 3 study (N = 12), vestronidase alfa 4 mg/kg administered intravenously every other week (QOW) for 24 weeks significantly reduced urinary GAG (uGAG) excretion, and most subjects with MPS VII exhibited improvement in other clinical and patient-reported outcomes [ 8 , 9 ]. In the open-label, long-term extension, reductions in uGAG excretion were sustained, and treatment was well tolerated [ 10 ].…”
Section: Introductionmentioning
confidence: 99%